Studi Perbandingan Kinerja Sistem Struktur Setback berdasarkan Metode ATC 40, FEMA 356 dan SNI 1726:2012 - Elias G Arman; Remigildus Cornelis; Tri M Sir (Universitas Nusa Cendana, 2021)
The aim of this study was to compare the performance level of the setback structure system and the non-setback structural system using the ATC-40, FEMA 356 and SNI 1726-2012 methods. The non-setback structure have the shortest span of 15 m, the longest span of 20 m and the level of each floor was 3.5 m but the setback structure have setback system on the longest span of 10 m at the 5th and 6th floor level. The results showed that the performance level based on all methods of the sectback structure system is at the immediate occupancy level while the non-setback structure system, based on SNI 1726-2012, the performance level is immediate occupancy for the longest span and the shortest span is damage control. On the other hand, based on the ATC-40 and FEMA 356 methods, the performance level of the non-setback structure is at the immediate occupancy level. Drift on non-setback buildings based on the SNI 1726-2012 method is 0.011, based on the ATC-40 method is 0.007, and based on FEMA 356 is 0.005. Drift on the setback building based on the SNI 1726-2012 method is 0.010, based on the ATC-40 method is 0.006, and based on FEMA 356 is 0.004.